A Bayesian approach to demand forecasting for new equipment programs. (October 2017) - Bergman, Jennifer J.; Noble, James S.; McGarvey, Ronald G.; Bradley, Randolph L.
Abstract: Demand forecasting is a fundamental component in a range of industrial problems (e.g., inventory management, equipment maintenance). Forecasts are crucial to accurately estimating spare or replacement part demand to determine inventory stock levels. Estimating demand becomes challenging when parts experience intermittent demand/failures versus demand at more regular intervals or high quantities. In this paper, we develop a demand forecasting approach that utilizes Bayes' rule to improve the forecast accuracy of parts from new equipment programs where established demand patterns have not had sufficient time to develop. In these instances, the best information available tends to be "engineering estimates" based on like /similar parts or engineering projections. A case study is performed to validate the forecasting methodology. The validation compared the performance of the proposed Bayesian method and traditional forecasting methods for both forecast accuracy and overall inventory fill rate performance. The analysis showed that for specific situations the Bayesian-based forecasting approach more accurately predicts part demand, impacting part availability (fill rate) and inventory cost. This improved forecasting ability will enable managers to make better inventory investment decisions for new equipment programs. Highlights: Addresses situations were engineering estimates are used to estimate initial part. Develops a Bayesian methodology to improve demand forecasting of spare parts for new equipment programs. Illustrates the importance of evaluating true fill rate performance in comparative studies. Supports better inventory investment budgeting as estimates of demand are refined over time. Demonstrates improved performance and cost savings of utilizing a Bayesian approach.